W kręgu badań nad sztuką portretową XVIII wieku - Moryń, Hanna (Wydawnictwo Naukowe UAM, 1995)
Marcia Pointon, Hanging the Head. Portraiture and Social Formation in Eighteenth-Century England, New Haven & London 1993, Yale University Press, 278 ss., 292 il.

Barbara Maria Stafford, Body Criticism. Imaging the Unseen in Enlightenment Art and Medicine, Cambridge, Massachusetts 1991, Massachusetts Institute of Technology, 586 ss., 247 il. Richard Wendorf, The Elements o f Life. Biography and Portrait-Painting in Stuart and Georgian England, Oxford 1990, Clarendon Press, 308 ss., 76 il.

Roland Kanz, Dichter und Denker im Portrat. Spuregange zur deutschen Portratkultur des 18. Jahrhunderts, München 1993, Deutscher Kunstverlag, 277 ss., 82 il.